# Find the followin

(i)

x (x + 7) + 4 (x + 7)

= x2 + 7x + 4x + 28

= x2 + 11x + 28

(ii)

x (x + 4) – 11 (x + 4)

= x2 + 4x – 11x – 44

= x2 – 7x - 44

(iii)

x (x – 5) + 7 (x – 5)

= x2 – 5x + 7x – 35

= x2 + 2x - 35

(iv)

x (x – 2) – 3 (x – 2)

= x2 – 2x – 3x + 6

= x2 – 5x + 6

(v)

y2 (y2 – 3) – 4 (y2 – 3)

= y4 – 3y2 – 4y2 + 12

= y4 – 7y2 + 12

(vi)

x (x + ) + (x + )

= x2 + + +

= x2 + + + 1

= x2 + + 1

(vii)

3x (3x + 11) + 5 (3x + 11)

= 9x2 + 33x + 15x + 55

= 9x2 + 48x + 55

(viii)

2x2 (2x2 – 5) – 3 (2x2 – 5)

= 4x4 – 10x2 – 6x2 + 15

= 4x4 – 16x2 + 15

(ix)

z2 (z2 – 3) + 2 (z2 – 3)

= z4 – 3z2 + 2z2 – 6

= z4 – z2 - 6

(x)

3x (2x – 4y) – 4y (2x – 4y)

= 6x2 – 12xy – 8xy + 16y2

= 6x2 – 20xy + 16y2

(xi)

3x2 (3x2 – 3xy) – 4xy (3x2 – 3xy)

= 9x4 – 9x3y – 12x3y + 12x2y2

= 9x4 – 21x3y + 12x2y2

(xii)

x (x + ) + 5 (x + )

= x2 + + 5x + 1

= x2 + x + 1

(xiii)

z (z + ) + (z + )

= z2 + z + z +

= z2 + z + z + 1

= z2 + z + 1

(xiv)

x2 (x2 + 9) + 4 (x2 + 9)

= x4 + 9x2 + 4x2 + 36

= x4 + 13x2 + 36

(xv)

y2 (y2 + 6) + 12 (y2 + 6)

= y4 + 6y2 + 12y2 + 72

= y4 + 18y2 + 72

(xvi) (y2 + ) (y2 - )

y2 (y2 - ) + (y2 - )

= y4 - y2 + y2 – 2

= y4 - y2 - 2

(xvii)

p2 (p2 - ) + 16 (p2 - )

= p4 p2 + 16p2 – 4

= p4 - p2 - 4

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

State whether theNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

What must be addeRD Sharma - Mathematics

Divide:

<p
RD Sharma - Mathematics

Divide:

<p
RD Sharma - Mathematics

Divide:

<p
RD Sharma - Mathematics